Faktor-faktor Histopatologik yang Memengaruhi Metastasis ke Kelenjar Getah Bening pada Karsinoma Sel Skuamosa Laring di Departemen Patologi Anatomik FKUI/RSCM Tahun 2015-2019 - Ela Laelasari; Lisnawati (Perhimpunan Dokter Spesialis Patologi Indonesia (IAPI), 2022)
BackgroundLaryngeal squamous cell carcinoma (LSCC) is the second most common epithelial carcinoma of the head and neck. This carcinomahas a poor prognosis if there have been metastases in the neck lymph nodes and did not get proper therapheutical management.The aims of the study is to determine the histopathologic characteristics of LSCC with partial or total laryngectomy and neckdissection, as well as its relationship with the incidence of metastases to lymph nodes.MethodsAnalytical descriptive study with cross-sectional design of secondary data on LSCC cases obtained through total or partiallaryngectomy accompanied by neck dissection from the archives of the Department of Anatomic Pathology FKUI / RSCM fromJanuary 2015 to December 2019. The histopathological data obtained were analyzed by comparative statistical test.ResultsKSSL was more frequently found in men as much as 155 cases (94.5%) with the most common age was over 60 years old. In thisstudy, LSCC with lymph nodes metastases was found in 65 cases, the most common was tumor size >4 cm in 40 cases (61.5%),medium differentiated tumors in 47 cases (72.3%), pT3-pT4 in 57 cases. (87.7%). There was a significant association betweenmetastasis to cervical lymph nodes with tumor size, poorly differentiated tumors, lymphovascular invasion and pT3-pT4.ConclusionHistopathologic factors including tumor size, pT3-pT4, poor differentiation, lymphovascular invasion are factors that play a role in theoccurrence of metastases to cervical lymph nodes in LSCC